DESIGN AND ANALYSIS OF BUCK BOOST CONVERTER WITH MODIFIED TOPOLOGY FOR PV APPLICATION - Bhavsar Gaurav; Dhikale Vaibhav; Thakekar Kunal (International Journal of Innovations in Engineering Research and Technology, 2021)
Design of Two switch buck boost converter which will operate on PV system. The proposed converter is used between PV system and load. The converter can operate in both buck as well as boost mode. Changing its mode is possible by controlling gate signals of respective semiconductor switch. As we get the voltage as per requirement at the output of converter we overcome problem of variation in voltage from system. We can overcome the problem of the voltage variation of the electrical output from PV system. Eventually there have been much advancement in solar technology but the technological advancements are still needed for various renewable energy systems for different loading conditions. By using this TSBB convertor, we can get voltage as per requirement which is helping for distribution the electricity during any environmental condition. MATLAB simulated model with PV system followed by converter is presented. Design of converter is for variable input from PV system, according to input obtained output is varied between range of 12 V to 40 V. Position of two semiconductor switches is arranged in such a way that their source is directly connected to the ground leads to give broader selection range for gate driver IC. As in each mode we use only one semiconductor for switching purpose overall performance is improved